A narrated emergence : a complex urban Integration of an informal settlement in Moreleta Park, Pretoria with its surrounding context - Shand, Dayle Lesley (University of Pretoria, 2023)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2022.